Clinical efficacy and safety evaluation of camrelizumab plus lenvatinib in adjuvant therapy after hepatocellular carcinoma surgery - Wang, Xudan; Cao, Weiwei; Qiu, Yan; Ji, Hongchen; Yuan, Juzheng; Wu, Weikang; Liu, Fuyuan; Feng, Liangyong; Ding, Rui; Li, Xiao; Tao, Kaishan (Frontiers in Oncology, 2023)
Objective To assess the efficacy and safety of camrelizumab plus different targeted drugs in adjuvant therapy after hepatocellular carcinoma (HCC) surgery. Patients and methods This retrospective cohort study included HCC patients who, after undergoing failed postoperative adjuvant lenvatinib therapy, received intravenous camrelizumab 200 mg every 3 weeks (C group, n = 97), camrelizumab plus oral apatinib 250 mg daily (C+A group, n = 125), camrelizumab plus oral lenvatinib 12 mg daily (for bodyweight ≥60 kg)/lenvatinib 8 mg daily (for bodyweight <60 kg) (C+L group, n = 120), or camrelizumab plus oral sorafenib 400 mg bi-daily (C+S group, n = 114) between October 2020 and October 2021. The outcomes including the objective response rate (ORR) and disease control rate (DCR) were evaluated by RECIST 1.1 and iRECIST. The median progression-free survival (mPFS), median overall survival (mOS), 6-month OS rate, 12-month OS rate, and adverse events were evaluated. Results As of 31 May 2022 with last follow-up time, the ORR was 17.2% for the C group, 44.6% for the C+A group, 47.9% for the C+L group, and 36.3% for the C+S group. The DCR was 72.0% for the C group, 81.8% for the C+A group, 85.5% for the C+L group, and 77.9% for the C+S group. The mPFS was 11.0 months (10.1–12.8) for the C group, 14.0 months (12.7–16.5) for the C+A group, 18.0 months (16.9–20.1) for the C+L group, and 12.0 months (9.7–14.4) for the C+S group. The mOS was 13.0 months (11.6–15.3) for the C group, 17.0 months (15.8–19.4) for the C+A group, 19.0 months (17.7–20.2) for the C+L group, and 15.0 months (14.1–17.3) for the C+S group. Grade 3 or 4 treatment-related adverse events occurred in 14 patients (14.4%) for the C group, 10 patients (8.0%) for the C+A group, 5 patients (4.2%) for the C+L group, and 11 patients (9.6%) for the C+S group. The most common adverse events were fatigue and transaminitis. Conclusion Camrelizumab combined with lenvatinib as adjuvant therapy showed promising efficacy and manageable safety in HCC patients. It might be a potential adjuvant therapy or second-line treatment for these patients.